The Evaluation of the Implementation of PPLOP Development (Education Center Student Sports Training) Soccer Central Java - Kurniawan, Yudhistira Ade; Rustiadi, Tri; Hartono, Mugiyo (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aims to evaluate the antecedent which includes the background, planning of the coaching program, and the objectives of the coaching program in PPLOP Soccer Central Java, to evaluate transactions which include recruitment of trainers, recruitment of athletes, training programs, facilities and infrastructure, funding, consumption, coordination, transportation, and welfare of athletes coaching in PPLOP Soccer Central Java, and to evaluate outcomes which include the successful implementation of coaching in athlete achievement in PPLOP Soccer Central Java. The approach used in the evaluation of the countenance model, the source of research data, namely management, trainers, athletes. The results of the study are antecedent evaluations consisting of background, coaching program planning, and the objectives of the coaching program in PPLOP Soccer Central Java are clear and well-structured, transaction evaluations consisting of recruiting coaches and athletes have been going well, the coaching program has been running well good enough according to the scheduled training program, facilities and infrastructure are not good some do not yet have and are not national standards, funding is not going well enough not enough to meet the needs of coaching, consumption is still not good, coordination is going well, welfare for coaches and athletes is still not optimal , transportation is very lacking because it does not have transportation and the evaluation of outcomes is good enough, but not yet stable.